Pengembangan Media Pembelajaran Bahasa Arab Berbasis Video Modifikasi Dubbing Kartun Dengan Materi Hiwar Kelas VII MTs - Shofwah Tsania Zakiyah; Ardina Novitasari (Mahira: Journal of Arabic Studies & Teaching, 2023)
Little effort of educators utilizing learning media in the current digital era. This study is to provide a contribution of ideas regarding teaching materials that can be used in delivering learning materials, especially Arabic. This study aims to find out how to develop Arabic language learning media based on modified cartoon dubbing videos with Min Yaumiyyāt Al-Usrah material to find out the feasibility of Arabic language learning media based on modified cartoon dubbing videos on Min Yaumiyyāt Al-Usrah material to find out students' responses to Arabic language learning media based on modified cartoon dubbing videos with Min Yaumiyyāt Al-Usrah material. The research and development method uses a procedural development model. The subjects of this study were a Material Expert, a Media Expert and grade VII students. Data collection techniques and analysis using observation, documentation, interviews, and questionnaires. Data analysis techniques using the Miles and Hubberman model for qualitative data, and with descriptive percentage analysis techniques for quantitative data. This research produces a product in the form of Arabic language learning media based on modified cartoon dubbing videos developed. The results of the study also show that the developed learning media is declared very feasible. This is based on assessment by material experts with a percentage of 89.3% with Very Good criteria. And media expert assessment with a percentage of 95% with Very Good criteria. Student assessment through a response questionnaire, obtained an average score of 4.18 with a percentage of 83.7% so that it is classified as a positive response